Answer: Choice F) 1
=============================================
Step-by-step explanation:
x^2+8x+7 factors to (x+1)(x+7)
x^2+4x-21 factors to (x-3)(x+7)
Therefore, the numerator (x^2+8x+7)(x-3) updates to (x+1)(x+7)(x-3)
The denominator (x^2+4x-21)(x+1) updates to (x-3)(x+7)(x+1)
We have three pairs of terms that will cancel between the numerator and denominator. The (x+1) terms pair up and cancel out, so do the (x+7) terms and also the (x-3) terms as well. Everything cancels out. The only thing left is 1 because x/x = 1 where x is nonzero. We can have a more complicated expression replace x to get the same basic idea. This is what I mean by "canceling".